Synthesis of Quinolines and Dibenzo[b,f][1,5]Diazocines by MW-Assisted Solvent-Free Method - Choi, Soon-Kju; Yang, Jung-Woo; Lee, Do-Hun; Jung, Dai-Il; Hahn, Jung-Tai (Asian Journal of Chemistry, 2014)
Acetylpyridines, 2-acetylfuran, 2-acetylthiophene, acetyimidazoles, acetone and 4-methyl-acetophenone were condensed with 2-amino-4-bromobenzophenone (1) under the optimal reaction conditions. Condensation of 2a-j with 1 afforded quinolines in good yields (60-74.5 %). In these reactions, (5z,11z)-3,9-dibromo-6,12-diphenyl-dibenzo[b,f][1,5]diazocine (4) was isolated as the minor product. The self-condensation of 1 afforded 4 as the only product. In order to investigate the effect of DPP on product formation, the synthesis of 4 was carried out under microwave irradiation using different amounts (in equivalents) of DPP. The obtained yield of 4 was higher when using anhydrous DPP than when using HCl, H3PO4 and CH3COOH. The cyclization reaction proceeded very effectively in the presence of DPP, as shown in the two reaction mechanisms for the formation of quinolines and dibenzo[b,f][1,5]diazocine.